Mierolainen - Hops!; Filppula, Markku; Hokkanen, Timo J.; Järvinen, Erkki; Kauppinen, Esko; Kukkonen, Mika; Paulasto, Tuomo; Paulasto, Heli; Sallinen, Arto (Joensuun kelttiläisen musiikin ystävät, 2001)
14 kappaletta.